Experiência do usuário de longo prazo em plataforma de software crowdsourcing - Assmann, Márcia Prante (2021)
Crowdsourcing software development is commonly organized around platforms that allow an applicant to submit a task and connect it with a multitude of individuals, who will provide likely solutions to the task. However, these platforms often ignore factors that provide a satisfactory experience for the user, which reflects, among others, in the abandonment of tasks. Therefore, it is essential to identify and understand user experiences (UX) on platforms, to assist in the improvement/development of these environments and minimize barriers imposed by problems of unsatisfactory experiences. This dissertation aimed to investigate long-term UX in a crowdsourcing platform. This is an exploratory, qualitative study, carried out from a quasi-experiment, in which 10 undergraduate students selected by convenience participated. Participants performed tasks on the TopCoder platform over 3 months and answered an online questionnaire. Throughout the period, participants reported their experiences with the platform, describing their impressions of its use. The results showed that the most satisfying experiences occurred mainly in the last weeks of the study and were mainly associated with task completion and submission. For less satisfactory experiences, the main reasons identified were mainly associated with difficulty in use, low usability due to lack of knowledge. All participants stated that they would recommend the platform to others. It is concluded that, even with usability problems, in general, the users' experience when using the platform was satisfactory. The results can be used to suggest mechanisms that reduce the barriers imposed by problems of less satisfactory experiences, spreading crowdsourcing software and, consequently, expanding its adoption in the software development industry.